Telemedicine screening for cytomegalovirus retinitis at the point of care for human immunodeficiency virus infection - Jirawison C. (American Medical Association, 2015)
Copyright © 2015 American Medical Association. All rights reserved. IMPORTANCE Cytomegalovirus (CMV) retinitis is a leading cause of blindness in many developing countries, likely the result of inadequate screening. Telemedicine screening for CMV retinitis instituted at the point of care for human immunodeficiency virus (HIV) infection may allow for earlier detection. OBJECTIVES To determine the diagnostic accuracy of retinal photography in detecting CMV retinitis at the point of HIV care and to characterize the clinical manifestations of CMV retinitis detected through the screening program. DESIGN, SETTING, AND PARTICIPANTS We enrolled 103 participants from a population of 258 patients with HIV and a CD4 level of less than 100/ìL treated at an HIV clinic in Thailand from June 2010 through June 2012.We captured mosaic fundus photographs through a dilated pupil using a digital fundus camera. An experienced on-site ophthalmologist masked to the results of the fundus images subsequently examined each eye with indirect ophthalmoscopy and recorded the clinical findings on a standardized form. Three remote graders evaluated each image for CMV retinitis. INTERVENTION Fundus photography and indirect ophthalmoscopy. MAIN OUTCOMES AND MEASURES Sensitivity and specificity of telemedicine relative to indirect ophthalmoscopy for diagnosis of CMV retinitis and clinical features of CMV retinitis lesions. RESULTS Sixteen patients (15.5%) were diagnosed as having CMV retinitis, of whom 5 (31%) had bilateral disease. Of the 21 eyes (10.2%) with CMV retinitis, 7 (33%) had visual symptoms. Retinitis lesions occupied less than 10% of the total retinal surface area in 13 of 21 eyes (62%) and did not involve the posterior pole (ie, zone 1) in 15 of 21 eyes (71%). Mean logMAR visual acuity in affected eyes was 0.41 (95%CI, 0.11-0.71; Snellen equivalent, 20/50 [95%CI, 20/25-20/100]). The mean sensitivity for the 3 remote graders in detecting CMV retinitis on fundus photography was 30.2%(95%CI, 10.5%-52.4%), and mean specificity was 99.1% (95%CI, 97.8%-100.0%). The CMV retinitis lesions missed by the remote graders (false-negative findings) were more likely to be small (P =.001) and located in the peripheral retina (P =.04). CONCLUSIONS AND RELEVANCE Patients undergoing screening at a clinic for HIV treatment had less extensive retinitis than patients in recent reports from an ophthalmology clinic. Retinal photography with the camera used in this study was not highly sensitive in detecting CMV retinitis but may identify disease with an immediate threat to vision. Improved accuracy will require a camera that can more easily image the peripheral retina.